Vascular function and nitrite levels in elderly women before and after hydrogymnastics exercises (Journal of Physical Education (Maringá), 2019)
The regular practice of physical exercise may reduce the oxidative stress and the risk factors for cardiovascular diseases. This study aims to evaluate serum levels of nitrite and changes in cerebral arterial resistance and cholesterol in elderly women submitted to hydrogymnastic training. The sample was composed of 40 women with overage age of 69.21 ±5.27 years old, separated randomly into an intervention and a control group. Nitrite concentration was analyzed through Griess reaction. The arterial resistivity was observed by Doppler ultrasound, and the cholesterol was determined using colorimetric enzymatic method. The water exercise program lasted 16 weeks. It was seen an increase in NO2 (p=0.003), reduction in right common carotid artery resistance (p=0.024), TC (p=0.003) and LDL (p=0.001) cholesterol in the WG. There was a negative correlation between NO3 and RVA, r = -0.221 and p=0.049 and between NO3 and CT (r = -0,269 and p=0,016) after intervention. The hydrogynmnastic program promoted favorable changes in nitrite levels, arterial resistivity and cholesterol in the elderly women.